2011
DOI: 10.1073/pnas.1007868108
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of long timescales and stereotyped behaviors in Caenorhabditis elegans

Abstract: Animal behaviors often are decomposable into discrete, stereotyped elements, well separated in time. In one model, such behaviors are triggered by specific commands; in the extreme case, the discreteness of behavior is traced to the discreteness of action potentials in the individual command neurons. Here, we use the crawling behavior of the nematode Caenorhabditis elegans to demonstrate the opposite view, in which discreteness, stereotypy, and long timescales emerge from the collective dynamics of the behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 27 publications
2
98
1
Order By: Relevance
“…This cannot be tested directly with the aphid data, which was limited to a relatively short time span. This tendency has, however, been observed in the nematode Caenorhabditis elegans when crawling on a surface and when swimming in water in the absence of external stimuli [165][166][167][168]. Salvador et al [168] also reported that meansquare displacements grew super-diffusively (as t 1.37 ) rather than ballistically (as t 2 ), as was expected for diffusivity growing linearly over time.…”
Section: Lévy Walks Could Results From Variation In Individual Correlamentioning
confidence: 81%
“…This cannot be tested directly with the aphid data, which was limited to a relatively short time span. This tendency has, however, been observed in the nematode Caenorhabditis elegans when crawling on a surface and when swimming in water in the absence of external stimuli [165][166][167][168]. Salvador et al [168] also reported that meansquare displacements grew super-diffusively (as t 1.37 ) rather than ballistically (as t 2 ), as was expected for diffusivity growing linearly over time.…”
Section: Lévy Walks Could Results From Variation In Individual Correlamentioning
confidence: 81%
“…It was recently shown that the space of shapes adopted by the nematode C. elegans is low dimensional, and that these dimensions (‘eigenworms’) can provide a quantitative description of behavior (Stephens et al, 2008). This exquisitely sensitive analysis revealed the underlying simplicity of complex locomotion dynamics as well as subtle behavioral phenotypes that had been previously undetectable (Stephens et al, 2010, 2011; Brown et al, 2013). However, this analysis does not provide an intuitive interpretation of the detected phenotypes that may directly relate to the underlying neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…One should interpret this approach as a projection or reduction of motor behaviors onto four templates or parameters with variable strengths. Mapping the dynamics of the shape space to the trajectory of the moving worm can reveal subtle differences in locomotion (Stephens et al, 2010;Stephens et al, 2011).…”
Section: Eigenworms: Low-dimensional Superposition Of Principal Compomentioning
confidence: 99%